2014
DOI: 10.1016/j.oooo.2014.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SOX2 as a potential marker for ameloblastic carcinoma

Abstract: The diffuse nuclear staining pattern of SOX2 is suggestive of a high-grade process in ameloblastic neoplasms. Numerous aggregates of cells harboring dense nuclear stain should raise concern for a malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 28 publications
5
53
0
Order By: Relevance
“…More recently a study explored using SOX2 (sex determining region-Y-related high mobility group box2) immunohistochemical nuclear staining as a marker to identify areas in high-grade transformation in ameloblastic neoplasms [17]. The investigators used a scoring system with two parameters, percent of nuclei staining and intensity of staining.…”
Section: Ameloblastic Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…More recently a study explored using SOX2 (sex determining region-Y-related high mobility group box2) immunohistochemical nuclear staining as a marker to identify areas in high-grade transformation in ameloblastic neoplasms [17]. The investigators used a scoring system with two parameters, percent of nuclei staining and intensity of staining.…”
Section: Ameloblastic Carcinomamentioning
confidence: 99%
“…Prior to this study the proliferative marker Ki-67 has been found to be markedly higher in AC than AB. The investigators concluded that use of SOX2 in conjunction with Ki-67 would aid in separating AC from AB and AA [17] (Fig. 2).…”
Section: Ameloblastic Carcinomamentioning
confidence: 99%
“…Thus, morphological features including the cytological features of malignancy and a prominent infiltrative and destructive growth pattern are likely to be more useful [16]. However, a number of newer immunohistochemical markers have been suggested, such as nuclear SOX2 expression [47], and these may prove useful markers to identify malignant ameloblastic tumours.…”
Section: Malignant Odontogenic Tumorsmentioning
confidence: 99%
“…Yoon et al (29) found that the expression of cytokeratin 18, parenchymal matrix metalloproteinase (MMP)-2, stromal MMP-9 and Ki-67 differentiate AC from ameloblastoma. Lei et al (30) recommend the inclusion of SOX2 immunohistochemical staining in conjunction with Ki-67 in challenging cases with atypical features. Locally the tumor is invasive, often showing a silent infiltrative growth (30).…”
Section: Discussionmentioning
confidence: 99%